Nursing Care of the Acute Ischemic Stroke Endovascular Thrombectomy Patient. Issue 9 (20th June 2022) - Hill, Michelle; Baumann, JJ; Newcommon, Nancy
Abstract : Nurses are an integral part of the multidisciplinary team caring for a patient eligible for endovascular thrombectomy. Their care includes obtaining health history, performing clinical assessments, using critical thinking to anticipate the care path, and communicating findings to other team members. The prehospital and emergency department nurses utilize stroke severity scales to identify a possible thrombectomy candidate and help expedite intervention. In the interventional laboratory, nursing collaborates with radiology technologists and interventionalists to ensure patient safety and monitor for intraprocedural complications. Post-procedure, the intensive care nurse delivers complex care to ensure optimal neurological outcome and assess for postprocedural complications. Nursing is essential in every phase of care along with collaboration with other disciplines.